ASSOCIATION BETWEEN POLYMORPHISMS IN GENES ENCODING 2′-5′-OLIGOADENYLATE SYNTHETASES AND THE HUMORAL IMMUNE RESPONSE UPON VACCINATION AGAINST TICK-BORNE ENCEPHALITIS - N. S. Yudin; A. V. Igoshin; S. L. Lutova; Ya. Gon; M. I. Voevoda; V. A. Belyavskaya (Вавиловский журнал генетики и селекции)
Vaccination forms active immunity and represents an effective way of preventing tick-borne encephalitis (TBE). However, excessive vaccination is unjustified in terms of economics and medical ethics. One of the individualized approaches to vaccines is the selection of vaccine doses depending on the expected levels of immune response. Therefore, there is a need for new methods for assessing potential human immune responses prior to vaccination. The aim of this study was to determine possible association between single nucleotide polymorphisms (SNPs) located within OAS2 and OAS3 genes, which have been previously associated with the development of severe forms of TBE, and the formation of antibodies and cytokines upon vaccination against TBE. The study involved 97 volunteers of both sexes who had not previously been vaccinated against TBE and had no contact with ticks. Venous blood samples were collected one month after vaccination against TBE using the EnceVir vaccine. Levels of specific IgG antibodies against tick-borne encephalitis virus and interleukin 4 (IL-4) were analyzed. Genomic DNA samples were genotyped for the SNPs rs2285932, rs2072136, rs1293762, rs15895 and rs1732778 in genes encoding 2’-5’-oligoadenylate synthetases OAS2 and OAS3. Antibody production in response to vaccine administration was significantly associated with SNP rs1732778 in the regulatory region of the OAS2 gene. This indicator was significantly higher in people with heterozygous genotypes G/A as compared to people with homozygous genotypes G/G and A/A. Carriers of the A allele (G/A or A/A genotypes) of the same SNP had reduced IL-4 levels as compared to the homozygous G/G individuals. Thus, the data obtained indicate that SNP rs1732778 in the regulatory region of the OAS2 gene correlates with the formation of antiviral IgG antibodies and changes in IL-4 levels upon vaccination. Evidently, the genetic polymorphism in OAS2 gene should be considered when performing individualized TBE vaccinations.